Parental Support and Growth Mindset as Predictors of Career Maturity in Early Adult Women in Indonesia: Bootstrap Linear Regression Analysis - Rahma Anindya Irawan; Intan Islamia; Khoiriyah Ulfah; Ahmad Zarkasi (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study investigates the influence of parental support and a growth mindset on career maturity among early-adult women in Indonesia. Previous research has rarely examined the simultaneous contributions of internal and external factors to career maturity in this demographic group. Using a quantitative correlational design, 385 women aged 18–25 years participated through purposive sampling. Instruments included the Career Maturity Inventory–Revised (CMI-R), the Career-Related Parent Support Scale, and the Growth Mindset Scale. Data were analyzed using linear regression bootstrap. Results indicated that parental support (β = 0.439, p < 0.001) and growth mindset (β = 0.315, p < 0.001) significantly predicted career maturity, explaining 29.19% of the variance (R² = 0.445). These findings highlight the role of family support and cognitive beliefs in shaping women's career readiness. Practical implications include the need for career counselors and parents to create supportive environments that foster career exploration and decision-making. Limitations include reliance on self-report measures and a non-random sample. Future studies are recommended to use longitudinal designs and include broader demographic groups. Keywords: career maturity, emerging adulthood woman, growth mindset, parental support